2013
DOI: 10.3923/pjn.2013.957.959
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Antinutritional Components of Vetiver Grass (Chrysopogon zizanioides L. Roberty) at Different Stages of Growth

Abstract: Vetiver grass was harvested at 4, 6 and 8-week old re-growth. The chemical composition and quantitative analyses of anti-nutritional components were determined. The result showed that dry matter and fiber content increased with age while crude protein, mineral content and anti-nutritional components reduced with age. It was concluded that age of re-growth significantly affect the nutrient and anti-nutrients contents of vetiver grass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
5
3
Order By: Relevance
“…The concentration of oxalate in P. pedicellatum grass is 1.00 ± 0.0008 mg/100 g DW. The value is higher compared to the value obtained for Pennisetum purpureum (0.159 ± 0.010 mg/100 g DW) as reported by Okaraonye and Ikewuchi (2009) and also higher than what was obtained for Vetiver grass (0.25 ± 0.03 mg/100 g DW) reported by Falola et al (2013). High oxalate content causes irritation in the mouth and interfere with the absorption of divalent minerals particularly calcium by forming insoluble salts with them leading to kidney stone which may eventually lead to death (Hassan et al, 2007).…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…The concentration of oxalate in P. pedicellatum grass is 1.00 ± 0.0008 mg/100 g DW. The value is higher compared to the value obtained for Pennisetum purpureum (0.159 ± 0.010 mg/100 g DW) as reported by Okaraonye and Ikewuchi (2009) and also higher than what was obtained for Vetiver grass (0.25 ± 0.03 mg/100 g DW) reported by Falola et al (2013). High oxalate content causes irritation in the mouth and interfere with the absorption of divalent minerals particularly calcium by forming insoluble salts with them leading to kidney stone which may eventually lead to death (Hassan et al, 2007).…”
Section: Resultscontrasting
confidence: 69%
“…The mineral composition of Pennisetum pedicellatum is represented in Table 1. The concentration of sodium in P. pedicellatum grass was found to be 111.67 mg/100 g which is higher than the value (96.56 mg/100 g) reported by Waziri et al (2013) on the analysis of Andropogon gayanus grass and also what was reported by Falola et al (2013) for vetiver grass (Chrysopogon zizanioides). On the other hand, the value is lower than what was reported for Cassia hirtsutse (421.05 mg/100 g) as reported by Akpabio et al (2012).…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Khus has biocide properties, protecting other crops from detrimental fungi such as Rhizoctonia solani (Dubey et al, 2010), and can also act as termite repellent (Zhu et al, 2001). Apart from its ecological and economic benefits, vetiver can further be used as fodder for livestock (Falola et al, 2013), roof covering (Gnansounou et al, 2017), and to produce ropes, several types of handicrafts (Danh et al, 2012;Gnansounou et al, 2017) and pulp and paper (Darajeh et al, 2019). Furthermore, having a potential biomass production in optimal conditions of over 100 tonnes ha −1 yr −1 , vetiver can be used for e.g., producing electricity, while providing environmental benefits through soil carbon sequestration (Danh et al, 2012).…”
Section: Perennial Grass Cropsmentioning
confidence: 99%
“…Molasses, sugar beet, bagasse and most recently sugar cane have been used as fermentation stimulant. Other additives such as wheat offal (Akinwande ., 2011), poultry litter, citrus pulp and cassava peels (Falola ., 2013) have been documented as ensiling material, however, cost and availability are often a limiting factor. Breadfuit (…”
Section: Eichhornia Crassipesmentioning
confidence: 99%